How to Apply Agile Principles to International Development M&E - ICTworks (2016)
We all want to be good at our jobs. We want to accomplish the things w e set out to do. If we aren’t accomplishing them, we want to figure ou t why or try new solutions. The trend toward Adaptive M&E is exactly t hat: a desire to be better at our jobs. Similar trends exist in the so ftware world (agile) and in manufacturing and start-ups (lean). But by any name, this process of seeking to improve is about speeding up dec ision-making and solution delivery by focusing on incremental, iterati ve planning and execution. I presented on agile with Monalisa Salib of USAID Learning Lab at MERL Tech 2016. I talked about creating softwar e; she talked about creating evaluation tools for USAID missions, but we were describing the same basic process: Develop, Release, Reflect, and Adapt. You can see our slide deck for more details, but here are t he key discussion takeaways that won’t show up there: 1: Eyes on the P rize Any effort should start with a clear definition of what you’re ho ping to achieve.
Keywords: IMPORTANT